ChemInform Abstract: Chemical Twinning of Salt and Metal in the Subnitridometalates Ba23Na11(MN4)4 with M: V, Nb, Ta. Issue 44 (13th October 2016) - Woersching, Matthias; Tambornino, Frank; Datz, Stefan; Hoch, Constantin
Abstract: The title compounds are prepared by solid state reaction of 8:5:2:15 molar mixtures of Ba2 N, Ba, M (M: V, Nb, Ta), and Na (Ta crucible, 500 °C).